Unmasking the hidden struggle: anxiety and depression in recovery of osteoarthritis knee - Rastogi, Aavrati; Kalia, Roop B.; Meena, Pradeep K. (International Journal of Research in Medical Sciences, 2026)
Background: A gradual degenerative condition that severely impairs mobility and quality of life is knee osteoarthritis (KOA). It has been hypothesized that mental health issues, including anxiety and depression, play a role in how OA symptoms are perceived and developed. The degree of the association is still undetermined, though. Methods: The study comprised one hundred individuals with KOA as defined by the EULAR classification. Age, gender and BMI were noted. With an emphasis on gender-based differences, this study compared the WOMAC (Western Ontario and McMaster Universities Osteoarthritis Index) scores of patients with osteoarthritis in the knee with mental health measures, specifically the PHQ-9 (Patient Health Questionnaire-9) for depression and the GAD-7 (Generalized Anxiety Disorder-7) for anxiety. Results: The study population's BMI was 27.19±4.31 kg/m² and their mean age was 56.34±8.81 years. Overall, the correlation between PHQ-9 and WOMAC was small (R=-0.026, p value=0.79), with males exhibiting a poor correlation (R=0.043, p value=0.80) and females exhibiting a moderate but non-significant positive correlation (R=0.374, p value=0.33). Overall, there was no significant correlation between GAD-7 and WOMAC (R=-0.13, p value 0.20), with a weak positive correlation in females (R=0.075, p value=0.55) and an insignificant correlation in men (R=-0.16, p value=0.35). Conclusions: While mental health factors like depression may influence OA severity in females, this study found no significant relationship between anxiety levels and WOMAC scores.